SUCCESSFUL TREATMENT OF ENDOBRONCHIAL TUBERCULOSIS IN PERSAHABATAN NATIONAL RESPIRATORY REFERRAL HOSPITAL - Sari, Adistya; Aniwidyaningsih, Wahju; Burhan, Erlina (Jurnal Respirologi Indonesia, 2020)
Backgrounds: Endobronchial tuberculosis (EBTB) is a special form of respiratory tuberculosis that continues to be a health problem because bronchostenosis may develop as a serious complication despite efficacious antituberculosis chemotherapy. The EBTB has nonspesific signs and symptoms, therefor it may cause misdiagnosis and delayed diagnosis. Persahabatan National Respiratory Referral Hospital doesn?t have data about successful treatment of EBTB Methods: This was a retrospective study of EBTB patients based from the medical record and confirm with bronchoscopy data from January 2013 to December 2017. Endobronchial tuberculosis diagnosed based from microbiology, histopathology examination or based on combination of clinical symptoms, radiology and bronchoscopy lesion appearance. Endobronchial tuberculosis treatment considered successful if there is improvement in clinical symptoms, microbiological conversion, accompanied by improvement or no change in the number of lesions or the radiological appearance. Results: The study sample consisted of 30 subjects. Majority of the subjects were female (86,7%), age